A socio-spatial perspective on fostering a sense of belonging among refugee families resettled in Canadian small cities - Karen M. Frensch; Bree Akesson (Wellbeing, Space and Society)
Fostering a sense of belonging plays a significant role in supporting refugee families’ integration into resettlement communities. The spatial dimensions within which refugees live and interact, such as homes, neighbourhoods, communities, and cities are influential in fostering belonging and supporting overall wellbeing. However, a socio-spatial perspective on belonging for refugees remains underdeveloped. To address this gap, we conducted an integrative knowledge synthesis of key sources from 2012 to 2022 contributing to the discourse on fostering refugee belonging via socio-spatial initiatives. Our aims were to highlight elements of belonging for refugee families that inherently embody the importance of place and to make recommendations for resettlement policy and practice. We focus on the size and socio-spatial characteristics of resettlement contexts to foster refugee families’ sense of belonging. Acknowledging the interconnectedness of belonging, notions of place, and integration can enhance resettlement processes and support the overall wellbeing of refugee families.